2023
DOI: 10.21037/atm-23-432
|View full text |Cite
|
Sign up to set email alerts
|

Association and predictive value of soluble thrombomodulin with mortality in patients with acute respiratory distress syndrome: systematic review and meta-analysis

Abstract: Background: Acute respiratory distress syndrome (ARDS) is a heterogeneous illness that has a high mortality rate. The role and predictive value of soluble thrombomodulin (sTM) in ARDS mortality is disputable, so the present study aimed to evaluate the association and predictive value of sTM for the inhospital mortality of ARDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Evidence from a study on rats with septic peritonitis suggests that recombinant human thrombomodulin (rhTM) can reduce mortality and lessen the severity of ALI, likely due to its anti-inflammatory and anticoagulant properties [79]. A systematic review and metaanalysis, involving a total of 13 studies, was conducted to assess the association and predictive value of soluble thrombomodulin (sTM) levels for mortality in ARDS patients; the results showed that elevated sTM levels were linked to a higher mortality risk [80]. The results of another study that included children with acute respiratory failure who were receiving mechanical ventilation showed that higher thrombomodulin levels were linked to higher mortality and organ dysfunction [81].…”
Section: Thrombomodulinmentioning
confidence: 99%
“…Evidence from a study on rats with septic peritonitis suggests that recombinant human thrombomodulin (rhTM) can reduce mortality and lessen the severity of ALI, likely due to its anti-inflammatory and anticoagulant properties [79]. A systematic review and metaanalysis, involving a total of 13 studies, was conducted to assess the association and predictive value of soluble thrombomodulin (sTM) levels for mortality in ARDS patients; the results showed that elevated sTM levels were linked to a higher mortality risk [80]. The results of another study that included children with acute respiratory failure who were receiving mechanical ventilation showed that higher thrombomodulin levels were linked to higher mortality and organ dysfunction [81].…”
Section: Thrombomodulinmentioning
confidence: 99%